Google Trends data analysis of hepatitis B and their correlation with hepatitis B early detection program for pregnant women in Indonesia - Nugraha, Dwi Adhi; Pramana, Triyanta Yuli (Universitas Gadjah Mada, 2022)
Purpose: Hepatitis B is still a problem in Indonesia. National surveillance project [Basic health survey (Riskesdas)] data in 2013 showed the prevalence of hepatitis B surface antigen (HBsAg) was 7.1%. One effort has been made to reduce the transmission of hepatitis B: the hepatitis B early detection program (DDHB) for pregnant women. Early changes in population health may be reflected in shifts in information and communication patterns on the internet. Changes in information and communication patterns on the internet can be an early